Möjligheter till energibesparingar på Södra Cell Värö med inriktning på indunstningen - Lindsten, Henrik (My University, 2004)
Södra Cell Värö is a pulp mill that produces kraft pulp for sale. Kraft mills use large amounts of fuel energy and discharge a lot of hot wastewater. Improved heat exchanging where some of the heat content in the wastewater streams is used can decrease the fuel energy demand in the process. Another option for energy savings is to use the excess heat in the evaporation plant, which is a process that consumes a lot of energy. Recent studies show that excess heat can be used in the evaporation plant to replace live steam, which leads to fuel savings or increased backpressure electricity production. A third option is to use the excess heat for production of district heating. The aim with this study was to explore the possibilities to make the evaporation plant and the entire mill more energy efficient. The possibilities to increase the production of district heating have also been explored. This was done by creating a computer model that simulates the evaporation at Södra Cell Värö and by performing a pinch analysis of the entire mill. The fuel supplied to a pulp mill is black liquor, bark and purchased fuel. An analysis of the fuel consumption at Södra Cell Värö shows that a decrease in steam consumption of more than 20 MW does not save any further fuel. This is due to the fact that the recovery boiler has to be in full operation to recover the chemicals. A 20 MW savings correspond to 11 MSEK/year. Suggestions how to improve the heat exchanger network using pinch analysis have been given and these together give total savings of about 3.5 MW, which correspond to about 3 MSEK/year. This study shows that almost 22 MW of excess heat can be made available for process integrated evaporation. If the 22 MW is used in a process integrated evaporation plant 26 MW will be saved, which exceeds the 20 MW that is the limit of fuel savings. The study shows that there is 46 MW of excess heat available for district heating if no excess heat is used in the evaporation plant. In the present situation the need for district heating is not of this magnitude. In conclusion measures in the heat exchanger network along with a combination of process integrated evaporation and increased district heating could be the most interesting solution from an economic point of view.
Keywords: Kemiteknik; Chemical Engineering